Progress and direction of 3D seismic exploration in Qintong Sag of Subei Basin - LIU Ming,XUE Ye,LIU Tiantian,ZHAO Sucheng,LAN Jiada,SHI Mengjun,YANG Fan (Youqicang pingjia yu kaifa)
Qintong Sag of Subei Basin has high abundance of oil and gas resources and great exploration potential, but the geological target has the complex characteristics of “thin, broken, small, scattered and hidden”. Since 1989, there is a series of seismic technical breakthroughs in this area. From conventional 3D to high-precision 3D for secondary acquisition, the acquisition method of “single point broadband receiving with digital geophone, medium surface element grid and high coverage times” is established, a series of processing technologies have been formed, such as sequential processing, improved SNR processing, improved resolution processing, structural-constrained mesh tomographic velocity modeling and reverse-time prestack depth migration imaging, etc., as well as the thin-bedded sandstone prediction technology with the waveform indication inversion of SP sensitive curves. Technological progress has promoted the transformation from simple structural reservoir to complex small fault block reservoir, and then to complex structure-lithology subtle reservoir exploration in Qintong Sag. The analysis shows that the high SNR, high resolution and amplitude-preserving processing effect are limited by the large difference of multi-phase data collection, narrow frequency band of original data and low sampling density of wave field. In order to solve the further problems of the complex subtle reservoir seismic exploration, wireless single-point receiving, single-point broadband excitation, small surface element, high coverage density, wide azimuth seismic acquisition, amplitude quantization quality control, broadband omni-directional processing and five-dimensional interpretation should be explored.